Research: The “Lost Mission” of African Universities - Andoh, Harris (International Higher Education, 2017)
The first universities in Africa were established with the triple mission of teaching, research, and community engagement. Yet, many university leaders hold the mistaken notion that their universities have always been research universities. It is only over the last decade that the research mission has emerged again as a key vision of African universities.